INTERAKSI SOSIAL PEKERJA PEREMPUAN DI USAHA PENGOLAHAN KOPRA (STUDI KASUS PADA USAHA PENGOLAHAN KOPRA DI PARIT NO.02 MULYA DESA KAYU RAJA) - Desti, Desti; Syafrizal, Syafrizal; Resdati, Resdati (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This research was conducted in Kayu Raja Village, Keritang District, Indragiri Hilir Regency, to know the activities of women workers in the copra processing business and describe the social interactions of women workers in the copra processing business. To obtain accurate data using descriptive qualitative research methods with data collection using in-depth interviews, direct observation, and documentation. The results of the analysis show that there are various kinds of work activities carried out in the copra processing business, starting from the process of opening the chest, cleavage, transportation, drying, collecting coconuts, gouging, the process of dividing the shell and the process of burning the surface which will become charcoal. Copra processing workers come from the Bugis tribe, so in interacting, they use symbols, namely the Bugis language. The analysis of research observations showed an excellent interaction between female workers in the copra processing business. Female workers are housewives who also have a role in the domestic sector, like housewives in general.